Rural Communication in Productive Innovation Processes Physalis Peruviana Aguaymanto in Arequipa - Cusihuaman-Sisa, Gregorio Nicolás; Pilares-Figueroa, Denis; Valdiglesias Calvo, Ronny; Cruz Zevallos, Edgard Antony (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This is the result of research financed by PROCIENCIA-CONCYTEC, whose objective is to analyze the rural communication forms in the processes of productive innovation and the positioning of the aguaymanto as a native product of the Peruvian Andes, to propose communication strategies in rural sectors of Arequipa, physalis peruviana is a fruit of Andean origin, whose properties and characteristics surpass other similar fruits; the method of analysis is qualitative-quantitative, of the correlational, transectional type, the exploration is carried out in five rural districts of Arequipa, applying 125 surveys and 10 interviews.